Avaliação de matérias-primas alternativas com ação ligante ou sinterizante para concretos refratários - Consonni, Leonardo Barbosa (Universidade Federal de São Carlos, 2020)
Refractory materials are used as linings in most equipment of heavy industries. As the latter are continuously seeking to reduce expenses in order to increase their energy efficiency and productivity, the evaluation of binding and/or sintering agents, which would reduce time and temperature of thermal treatments, besides providing better properties to refractories in a broad temperature range (600-1500°C), has been widely studied in last years. Considering these aspects, this work aimed to evaluate the viability of different raw materials (calcium carbonate, calcium hydroxide, aluminum lactate, dead-burnt magnesia, magnesia fumes) as alternative binding or sintering additives to calcium aluminate cement (CAC) in refractory castables, as CAC does not provide a sintering effect to refractory products at intermediate temperatures (600-1000°C). The developed compositions were submitted to mechanical and thermomechanical characterization tests, such as cold modulus of rupture (MOR) and hot modulus of rupture (HMOR) after thermal treatment at different temperatures (50-1500°C), thermal shock (∆T ~ 1000°C), among others. Calcium carbonate and hydroxide did not provide an efficient binding effect (MOR 0.5-3.5 MPa), but their distinct sintering mechanisms (sintering-coarsening-coalescence process and CaO release, respectively) improved the mechanical and thermomechanical performance (MOR 8-40 MPa and HMOR 12-40 MPa) in a broad temperature range (600-1500°C). Dead-burnt magnesia and fumes provided a binding effect (MOR 2-12 MPa) due to brucite formation but sintering was limited in these castables. The mixture of calcium carbonate with magnesia fumes or aluminum lactate improved the green mechanical strength but reduced the sintering effect at intermediate temperatures (600-1000°C). These results showed the feasibility of replacing cement with the mixture of CaCO3 and aluminum lactate, what would bring economic effects with the reduction in the use of cement and the acquired performance.
Evaluation of alternative raw materials with binder or sintering action for refractory castables
Keywords: Concretos refratários; Alumina; Cimento; Agentes sinterizantes; Refractory castables; Alumina; Cement; Sintering agents; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS